Carbon-sequestration high-water-resistance gypsum product and preparation method thereof
Through the coordinated reaction of multiple solid waste and carbonization maintenance methods, the raw material ratio and process flow of gypsum products are optimized, and the problem of poor water resistance of gypsum products is solved, and gypsum products with high water resistance and strength are achieved, extending service life and reducing costs.
Patent Information
- Application Number
- CN202411914534.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The poor water resistance of existing gypsum products leads to a sharp decrease in strength when humidity increases, limiting their use and dosage.
Multi-solid waste collaborative reaction and carbonization curing methods are adopted to optimize the raw material ratio, including α-type short columnar semi-water gypsum, magnesium slag, calcium carbide slag, red mud, nano calcium carbonate and nano silica, the pores of the gypsum substrate are reduced, the pores are blocked, and micro calcium carbonate and silica gels are generated through carbonization reactions, filling and covering gypsum crystals.
It significantly improves the water resistance and strength of gypsum products, extends the service life, and reduces the product cost and avoids the risk of expansion and cracking.
Smart Images

Figure CN119613070A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solid waste resource utilization, and in particular to a carbon-fixing high-water-resistant gypsum product and a preparation method thereof. Background Art
[0002] Industrial waste gypsum is waste residue with calcium sulfate as the main component discharged by coal-fired power, chemical and other related industries, such as flue gas desulfurization gypsum, phosphogypsum, titanium gypsum, fluorinated gypsum, citric acid gypsum, salt gypsum, etc. With the increase in the output of industrial by-product gypsum year by year, the large-scale storage of industrial waste gypsum not only occupies land, but also wastes resources. The acid and other harmful substances contained in it are easy to pollute the surrounding environment, which has seriously affected and restricted the ecology. It is urgent to accelerate the resource utilization of industrial waste gypsum. Gypsum products prepared with gypsum as the base material have poor water resistance. With the increase of humidity, the strength of gypsum products decreases sharply. Therefore, the use and dosage of gypsum products are greatly limited. The fundamental reason for this phenomenon is: 1. Gypsum has a large solubility (2.05g CaSO4 is dissolved per liter of water at 20°C). When it is damp, due to the dissolution of gypsum, the bonding force between its crystals is weakened, thereby reducing the strength. Especially under the action of dynamic water, when water flows through or along the surface of gypsum products, the gypsum is dissolved and separated, and the strength reduction at this time cannot be restored. 2. Because the inner surface of the microcracks of the gypsum body absorbs moisture, the water film is coated on the surface of the gypsum crystal, so the micro units of each crystalline structure are separated. It is also regarded as the adsorption effect of gypsum on water. 3. The high porosity of gypsum materials will also aggravate the hygroscopic effect, because the hardened gypsum body will lose strength when loaded not only in pure water, but also in saturated and supersaturated gypsum solutions. In order to solve the problem of poor water resistance of gypsum, it is urgent to address the above three issues.
[0003] However, the existing technology still has some defects: 1. The surface of gypsum products is coated with silicone waterproof coating or paraffin wax. When the coating layer is damaged, the water resistance of gypsum products will drop sharply. 2. Organic hydrophobic substances are added to gypsum products. Although this technology can improve the water resistance of gypsum to a certain extent, the organic substances will affect the hydration properties of the gypsum itself, and will face the risks of unstable setting time and reduced product strength. 3. Although the addition of cement and other hydration-active adhesives can improve performance, it will increase costs and there is also the risk of expansion and cracking. 4. When using ordinary building gypsum (β-type semi-hydrated gypsum), a large amount of water is required during mixing, and the product itself is prone to produce more pores.
[0004] Currently, there is an urgent need to provide a new carbon-fixing and highly water-resistant gypsum product and a preparation method thereof. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a carbon-fixing high-water-resistant gypsum product and a preparation method thereof. The present invention adopts a multi-solid waste synergistic reaction and a carbonization curing method to prepare a carbon-fixing high-water-resistant gypsum product, and by optimizing the raw materials of α-type short columnar hemihydrate gypsum, magnesium slag, carbide slag, red mud, nano-calcium carbonate, nano-silicon dioxide and water and their dosage, the pores of the gypsum substrate itself can be reduced, the pores of the gypsum product can be blocked, and the gypsum crystals can be protected at a microscopic level, thereby solving the problem of poor water resistance of gypsum in multiple aspects.
[0006] In the first aspect, the present invention provides a carbon-fixing high water-resistant gypsum product, the raw materials of which include α-type short columnar semi-hydrated gypsum, magnesium slag, carbide slag, red mud, nano-calcium carbonate, nano-silicon dioxide and water; wherein the mass ratio of the α-type short columnar semi-hydrated gypsum, magnesium slag, carbide slag and red mud is 50~80:10~25:7.5~15:2.5~10. In the present invention, on the basis of α-type short columnar semi-hydrated gypsum, magnesium slag, carbide slag, red mud and other solid wastes are used for synergistic reaction, which can not only reduce the use of organic hydrophobic substances and cement adhesives, reduce the cost of gypsum products, but also improve the water resistance, strength and service life of gypsum products.
[0007] Preferably, the mass ratio of the α-type short columnar hemihydrate gypsum, magnesium slag, carbide slag and red mud is 50-80:15-25:12-15:6-10, preferably 50-60:15-20:12.5-15:7.5-10.
[0008] Preferably, the mass ratio of the α-type short columnar hemihydrate gypsum, nano-calcium carbonate and nano-silicon dioxide is 50-80: 0-0.05: 0-0.03, preferably 50-80: 0.02-0.05: 0.01-0.03.
[0009] Preferably, the mass ratio of the α-type short columnar hemihydrate gypsum to water is 50-80:30-40, preferably 50-80:30-38. In the present invention, by optimizing the usage ratio of the above raw materials, the water resistance, strength and service life of the carbon-fixing high water-resistant gypsum product can be further improved.
[0010] Preferably, the α-type short columnar hemihydrate gypsum has an aspect ratio of 1:1 to 1.5:1 and a particle size of 20 to 80 μm. In the present invention, the α-type short columnar hemihydrate gypsum can be prepared by a pressurized aqueous solution method, and preferably, the α-type short columnar hemihydrate gypsum has an aspect ratio of 1:1 to 1.5:1 and a particle size of 20 to 80 μm.
[0011] Preferably, the carbon-fixing high water-resistant gypsum product comprises the following raw materials in mass fractions: 50-80 parts of α-type short columnar hemihydrate gypsum, 10-25 parts of magnesium slag, 7.5-15 parts of carbide slag, 2.5-10 parts of red mud, 0.02-0.05 parts of nano-calcium carbonate, 0.01-0.03 parts of nano-silicon dioxide, and 30-38 parts of water. In the present invention, by optimizing the dosage of α-type short columnar hemihydrate gypsum, magnesium slag, carbide slag, red mud, nano-calcium carbonate, nano-silicon dioxide and water, the porosity of the gypsum substrate itself is further reduced, the pores of the gypsum product are better blocked, and the gypsum crystals are protected at the microscopic level, thereby solving the problem of poor water resistance of gypsum in multiple aspects.
[0012] Further preferably, the raw materials include the following parts by weight: 50-80 parts of α-type short columnar hemihydrate gypsum, 15-25 parts of magnesium slag, 12-15 parts of carbide slag, 6-8 parts of red mud, 0.04-0.05 parts of nano-calcium carbonate, 0.02-0.03 parts of nano-silicon dioxide, and 34-36 parts of water.
[0013] Preferably, the particle size of the α-type short columnar hemihydrate gypsum is 20-80 μm.
[0014] Preferably, the particle size of the magnesium slag and carbide slag is 5-20 μm.
[0015] Preferably, the particle size of the red mud is 15-30 μm.
[0016] Preferably, the particle size of the nano calcium carbonate is 60 to 100 nanometers.
[0017] Preferably, the particle size of the nano-silicon dioxide is 15 to 30 nanometers.
[0018] Preferably, carbonization gas is further included, wherein the volume concentration of carbon dioxide in the carbonization gas is 20% to 50%; preferably, the carbonization gas is waste gas containing carbon dioxide discharged from a factory. In the present invention, the specific amount of carbon dioxide gas is not specifically limited. The carbon dioxide is used for carbonization curing, and the amount commonly used in the art can be used. Preferably, the test block prepared from the above raw materials is placed in carbonization gas for at least one day of carbonization curing.
[0019] According to the present invention, the carbon-fixing high-water-resistant gypsum products mainly use α-type short columnar hemihydrate gypsum, which has well-developed crystals, low specific surface area, and low water demand during mixing. When the water demand is low, the gypsum hydration and hardening will reduce the pores generated by the gypsum matrix itself. This also reduces the possibility of water entering the interior of the gypsum product. The carbon-fixing reaction material (magnesium slag, carbide slag) will react with carbon dioxide during carbonization curing; magnesium slag contains dicalcium silicate, and its reaction chemical equation is: γC2S+2CO2 2CaCO3+SiO2; Carbide slag contains calcium hydroxide, and its reaction chemical equation is: Ca(OH)2+CO2 CaCO3+H2O; the calcium carbonate and silica gel produced can fill the pores inside the product, further blocking the entry of external water. Since the calcium carbonate and silica gel produced are smaller in size than gypsum crystals, they can be well attached to the surface of gypsum crystals, thus forming a coating and preventing the gypsum crystals from dissolving when they come into contact with water.
[0020] In a second aspect, the present invention provides a method for preparing the above-mentioned carbon-fixing and highly water-resistant gypsum products, comprising the following steps: premixing magnesium slag, carbide slag, α-type short columnar hemihydrate gypsum, nano-calcium carbonate, and nano-silicon dioxide to obtain a powder mixed sample; mixing and stirring the powder mixed sample with water to obtain a wet material slurry; pouring the wet material slurry and performing standard curing to obtain a test block; performing carbonization curing on the test block to obtain a carbon-fixing and highly water-resistant gypsum product.
[0021] Preferably, the carbonization curing time is 24-72 hours, the carbon dioxide concentration is 20%-50%, and the temperature is 20±2°C.
[0022] Preferably, the premixing time is 5 to 10 minutes.
[0023] Preferably, the stirring time is 120 to 240 seconds.
[0024] Preferably, the standard curing time is 2 to 8 hours.
[0025] Preferably, the method further comprises grinding magnesium slag, carbide slag and red mud separately for 20 to 35 minutes using a planetary ball mill.
[0026] Preferably, a 40×40×160 mm cement mortar three-piece mold is used for pouring, and then the poured cement mortar three-piece mold is placed in a cement standard curing box for curing.
[0027] The beneficial effect of the present invention is at least that: the carbon-fixing and highly water-resistant gypsum products provided by the present invention can reduce the porosity of the gypsum substrate itself, block the pores of the gypsum products, and protect the gypsum crystals from a microscopic level. The present invention adopts α-type short columnar hemihydrate gypsum to reduce the water demand of gypsum-based products and reduce the porosity of the products themselves. At the same time, multiple solid wastes such as magnesium slag, carbide slag, and red mud are used for synergistic reaction and carbonization curing, and the generated micro-sized calcium carbonate, silica gel, hydrated calcium silicate gel and other carbonization products and hydration products are filled in the pores between the overlapped gypsum crystals and attached to the surface of the gypsum crystals. The tiny carbonization and hydration products themselves will also overlap each other by physical and chemical bonding, further improving the overlap strength between the gypsum crystals. The present invention adopts multiple solid wastes and carbonization curing, which not only solves the problem of poor water resistance of gypsum products, but also provides new ideas for the coordinated disposal of multiple solid wastes and the effective utilization of greenhouse gases. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 1 is an image of α-type short columnar hemihydrate gypsum in an embodiment of the present invention.
[0030] Figure 2 This is a microscopic image of the interior of the carbon-fixing and highly water-resistant gypsum product provided in Example 3 of the present invention.
[0031] Figure 3 This is a microscopic image of the interior of a common gypsum product provided for Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0034] If no specific technology or conditions are specified in the examples of the present invention, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The experimental reagents and raw materials involved are all commercially available, and the reagents are all analytically pure products.
[0035] Example 1 The present embodiment provides a carbon-fixing high-water-resistant gypsum product, the raw materials of which are: 10 parts of magnesium slag, 7.5 parts of carbide slag, 2.5 parts of red mud, 80 parts of α-type short columnar hemihydrate gypsum, 0.02 parts of nano-calcium carbonate, 0.01 parts of nano-silicon dioxide, and 30 parts of water; wherein the α-type short columnar hemihydrate gypsum is prepared by a pressurized aqueous solution method, and its aspect ratio is 1:1-1.5:1, and its particle size is 20-80 μm ( Figure 1 ), the particle size of magnesium slag and carbide slag is 5~20μm; the red mud is the Bayer process red mud produced by the factory to produce alumina. After ball milling, the particle size of the red mud is 15~30μm; the particle size of nano calcium carbonate is 60~100 nanometers; the particle size of nano silicon dioxide is 15~30 nanometers; the water is (room temperature) tap water; the waste gas containing carbon dioxide discharged by the factory is used for carbonization curing, and the volume concentration of carbon dioxide is 20%.
[0036] This embodiment also provides a method for preparing the above-mentioned carbon-fixing high water-resistant gypsum product, the steps are as follows: Step 1: Put 10 parts of magnesium slag, 7.5 parts of carbide slag and 2.5 parts of red mud into a planetary ball mill and grind them for 20 minutes respectively.
[0037] Step 2: Put the ground magnesium slag, carbide slag, red mud, 80 parts of α-type short columnar hemihydrate gypsum, 0.02 parts of nano calcium carbonate, and 0.01 parts of nano silicon dioxide into a mixer and premix for 5 minutes to obtain a powder mixed sample.
[0038] Step 3: Put the powder mixed sample obtained in step 2 and 30 parts of water into a cement mortar mixer in turn and stir for 120 seconds to obtain a wet slurry.
[0039] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a standard cement curing box (temperature 20±2℃, relative humidity above 95%) for curing for 2 hours. After curing, demold the mold to obtain a test block.
[0040] Step 5: Place the test block obtained in step 4 into a carbonization box with a carbon dioxide concentration of 20% and a temperature of 20±2°C for 12 hours of curing, and obtain it after the curing is completed.
[0041] Example 2 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: Put 15 parts of magnesium slag, 10 parts of carbide slag and 5 parts of red mud into a planetary ball mill and grind them for 25 minutes respectively.
[0042] Step 2: Put the ground magnesium slag, carbide slag, red mud, 70 parts of α-type short columnar hemihydrate gypsum, 0.03 parts of nano calcium carbonate, and 0.01 parts of nano silicon dioxide into a mixer and premix for 6 minutes to obtain a powder mixed sample.
[0043] Step 3: Put the powder mixed sample obtained in step 2 and 32 parts of water into a cement mortar mixer in turn and stir for 160 seconds to obtain a wet slurry.
[0044] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 4 hours. After curing, demould the mold to obtain a test block.
[0045] Step 5: Place the test block obtained in step 4 into a carbonization box at a carbon dioxide concentration of 30% and a temperature of 20±2°C for 24 hours of curing. After the curing, a carbon-fixed and highly water-resistant gypsum product is obtained.
[0046] Example 3 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: Put 20 parts of magnesium slag, 12.5 parts of carbide slag and 7.5 parts of red mud into a planetary ball mill and grind them for 30 minutes respectively.
[0047] Step 2: Put the ground magnesium slag, carbide slag, red mud, 60 parts of α-type short columnar hemihydrate gypsum, 0.04 parts of nano calcium carbonate, and 0.02 parts of nano silicon dioxide into a mixer and premix for 8 minutes to obtain a powder mixed sample.
[0048] Step 3: The powder mixed sample obtained in step 2 and 34 parts of water are sequentially placed into a cement mortar mixer and stirred for 200 seconds to obtain a wet slurry.
[0049] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 6 hours. After curing, demould the mold to obtain a test block.
[0050] Step 5: Place the test block obtained in step 4 into a carbonization box at a carbon dioxide concentration of 40% and a temperature of 20±2°C for 56 hours of curing. After the curing, a carbon-fixed and highly water-resistant gypsum product is obtained.
[0051] Figure 2 This is a scanning electron microscope image of the carbon-fixed high-water-resistant gypsum product of this embodiment. It can be seen that the carbonization products and hydration products such as tiny-sized calcium carbonate, silica gel, hydrated calcium silicate gel, etc. fill the pores between the overlapping gypsum crystals and adhere to the surface of the gypsum crystals. The tiny carbonization and hydration products themselves will also overlap each other through physical and chemical bonding, further improving the overlapping strength between the gypsum crystals.
[0052] Example 4 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: Put 25 parts of magnesium slag, 15 parts of carbide slag and 10 parts of red mud into a planetary ball mill and grind them for 35 minutes respectively.
[0053] Step 2: Put the ground magnesium slag, carbide slag, red mud, 50 parts of α-type short columnar hemihydrate gypsum, 0.05 parts of nano calcium carbonate, and 0.03 parts of nano silicon dioxide into a mixer and premix for 8 minutes to obtain a powder mixed sample.
[0054] Step 3: Put the powder mixed sample obtained in step 2 and 38 parts of water into a cement mortar mixer in sequence and stir for 240 seconds to obtain a wet slurry.
[0055] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 8 hours. After curing, demould the mold to obtain a test block.
[0056] Step 5: Place the test block obtained in step 4 into a carbonization box with a carbon dioxide concentration of 50% and a temperature of 20±2°C for 64 hours of curing. After the curing, a carbon-fixed and highly water-resistant gypsum product is obtained.
[0057] Example 5 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: Put 20 parts of magnesium slag, 15 parts of carbide slag and 10 parts of red mud into a planetary ball mill and grind them for 30 minutes respectively.
[0058] Step 2: Put the ground magnesium slag, carbide slag, red mud, 55 parts of α-type short columnar hemihydrate gypsum, 0.04 parts of nano calcium carbonate, and 0.02 parts of nano silicon dioxide into a mixer and premix for 8 minutes to obtain a powder mixed sample.
[0059] Step 3: The powder mixed sample obtained in step 2 and 34 parts of water are sequentially placed into a cement mortar mixer and stirred for 200 seconds to obtain a wet slurry.
[0060] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 6 hours. After curing, demould the mold to obtain a test block.
[0061] Step 5: Place the test block obtained in step 4 into a carbonization box at a carbon dioxide concentration of 40% and a temperature of 20±2°C for 56 hours of curing. After the curing, a carbon-fixed and highly water-resistant gypsum product is obtained.
[0062] Example 6 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: Put 20 parts of magnesium slag, 12.5 parts of carbide slag and 7.5 parts of red mud into a planetary ball mill and grind them for 30 minutes respectively.
[0063] Step 2: Put the ground magnesium slag, carbide slag, red mud, 60 parts of α-type short columnar hemihydrate gypsum, 0.04 parts of nano calcium carbonate, and 0.02 parts of nano silicon dioxide into a mixer and premix for 8 minutes to obtain a powder mixed sample.
[0064] Step 3: The powder mixed sample obtained in step 2 and 34 parts of water are sequentially placed into a cement mortar mixer and stirred for 200 seconds to obtain a wet slurry.
[0065] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 6 hours. After curing, demould the mold to obtain a test block.
[0066] Step 5: Place the test block obtained in step 4 into a carbonization box at a carbon dioxide concentration of 30% and a temperature of 20±2°C for 60 hours of curing. After the curing, a carbon-fixed and highly water-resistant gypsum product is obtained.
[0067] Comparative Example 1 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: 100 parts of α-type short columnar hemihydrate gypsum and 30 parts of water are sequentially put into a cement mortar mixer and stirred for 120 seconds to prepare a wet slurry.
[0068] Step 2: Pour the wet slurry obtained in step 1 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 2 hours, demould after curing, and continue to place the test block into a cement standard curing box for curing for 70 hours after demoulding to obtain a gypsum test block.
[0069] Comparative Example 2 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: Put 15 parts of magnesium slag, 10 parts of carbide slag and 5 parts of red mud into a planetary ball mill and grind them for 25 minutes respectively.
[0070] Step 2: Put the ground magnesium slag, carbide slag, red mud, 70 parts of α-type short columnar hemihydrate gypsum, 0.03 parts of nano calcium carbonate, and 0.01 parts of nano silicon dioxide into a mixer and premix for 6 minutes to obtain a powder mixed sample.
[0071] Step 3: Put the powder mixed sample obtained in step 2 and 32 parts of water into a cement mortar mixer in turn and stir for 160 seconds to obtain a wet slurry.
[0072] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 4 hours, demould after curing, and continue to place the test block into the cement standard curing box for curing for 68 hours after demoulding to obtain a gypsum-based test block.
[0073] Comparative Example 3 The carbon-fixing high water-resistant gypsum product and preparation method are the same as those in Example 1, except that: Step 1: Put 25 parts of magnesium slag, 15 parts of carbide slag and 10 parts of red mud into a planetary ball mill and grind them for 35 minutes respectively.
[0074] Step 2: Put the ground magnesium slag, carbide slag and 50 parts of α-type short columnar hemihydrate gypsum into a mixer and premix for 8 minutes to obtain a powder mixed sample.
[0075] Step 3: Put the powder mixed sample obtained in step 2 and 38 parts of water into a cement mortar mixer in sequence and stir for 240 seconds to obtain a wet slurry.
[0076] Step 4: Pour the wet slurry obtained in step 3 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a cement standard curing box for curing for 8 hours. After curing, demould the mold to obtain a test block.
[0077] Step 5: Place the test block obtained in step 4 into a carbonization box with a carbon dioxide concentration of 50% and a temperature of 20±2°C for 64 hours of curing. After the curing, a carbon-fixed and highly water-resistant gypsum product is obtained.
[0078] Comparative Example 4 The gypsum product provided in this comparative example is prepared by the following method: Step 1: 100 parts of building gypsum (β-type hemihydrate gypsum) and 70 parts of water are sequentially put into a cement mortar mixer and stirred for 120 seconds to prepare a wet slurry.
[0079] Step 2: Pour the wet material slurry prepared in step 1 into a 40×40×160mm cement mortar three-piece mold, then place the poured cement mortar three-piece mold into a standard cement curing box for curing for 2 hours. After curing, demold the test block after demolding and continue to place it in a standard cement curing box for curing for 70 hours to obtain a gypsum test block.
[0080] Figure 3 This is the microscopic morphology of the common building gypsum product of comparative example 4. The hydrated gypsum crystals formed without the treatment of the present invention are coarse, the overlap between the crystals is loose, and there are many pores inside. External moisture can easily enter the interior of the product, resulting in poor water resistance of the common gypsum product.
[0081] The strength test of gypsum products refers to GB / T 17669.3-1999 "Determination of mechanical properties of building gypsum"; softening coefficient of gypsum products: softening coefficient = compressive strength in saturated water absorption state / compressive strength in dry state.
[0082] Table 1 Performance test results of various embodiments and comparative examples
[0083] After testing, it is found that the embodiment of the present invention can effectively solve the problem of poor water resistance of gypsum. Compared with the comparative example, the embodiment of the present invention can significantly improve the water resistance and strength of gypsum products, thereby extending the service life.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbon-fixing high water-resistant gypsum product, characterized in that: The raw materials of the carbon-fixing high-water-resistant gypsum product include α-type short columnar semi-hydrated gypsum, magnesium slag, carbide slag, red mud, nano-calcium carbonate, nano-silicon dioxide and water; wherein the mass ratio of the α-type short columnar semi-hydrated gypsum, magnesium slag, carbide slag and red mud is 50~80:10~25:7.5~15:2.5~10.
2. The carbon-fixing and highly water-resistant gypsum product according to claim 1, characterized in that: The mass ratio of the α-type short columnar hemihydrate gypsum, magnesium slag, carbide slag and red mud is 50-80:15-25:12-15:6-10.
3. The carbon-fixing and highly water-resistant gypsum product according to claim 1 or 2, characterized in that: The mass ratio of the α-type short columnar hemihydrate gypsum, nano calcium carbonate and nano silicon dioxide is 50-80: 0-0.05: 0-0.03; And / or, the mass ratio of the α-type short columnar hemihydrate gypsum to water is 50-80:30-40.
4. The carbon-fixing and highly water-resistant gypsum product according to any one of claims 1 to 3, characterized in that: The α-type short columnar hemihydrate gypsum has an aspect ratio of 1:1 to 1.5:1 and a particle size of 20 to 80 μm.
5. The carbon-fixing and highly water-resistant gypsum product according to any one of claims 1 to 4, characterized in that: The invention comprises the following raw materials in parts by weight: 50-80 parts of α-type short columnar hemihydrate gypsum, 10-25 parts of magnesium slag, 7.5-15 parts of carbide slag, 2.5-10 parts of red mud, 0.02-0.05 parts of nano calcium carbonate, 0.01-0.03 parts of nano silicon dioxide and 30-38 parts of water.
6. The carbon-fixing and highly water-resistant gypsum product according to claim 5, characterized in that: The invention comprises the following raw materials in parts by weight: 50-80 parts of α-type short columnar hemihydrate gypsum, 15-25 parts of magnesium slag, 12-15 parts of carbide slag, 6-8 parts of red mud, 0.04-0.05 parts of nano calcium carbonate, 0.02-0.03 parts of nano silicon dioxide and 34-36 parts of water.
7. The carbon-fixing and highly water-resistant gypsum product according to any one of claims 1 to 6, characterized in that: The particle size of the α-type short columnar hemihydrate gypsum is 20-80 μm; And / or, the particle size of the magnesium slag and carbide slag is 5-20 μm; And / or, the particle size of the red mud is 15-30 μm; And / or, the particle size of the nano calcium carbonate is 60 to 100 nanometers; And / or, the particle size of the nano-silicon dioxide is 15 to 30 nanometers.
8. The carbon-fixing and highly water-resistant gypsum product according to any one of claims 1 to 7, characterized in that: It also includes carbonized gas, in which the volume concentration of carbon dioxide is 20% to 50%.
9. The method for preparing the carbon-fixing high water-resistant gypsum product according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: premixing magnesium slag, carbide slag, α-type short columnar hemihydrate gypsum, nano calcium carbonate and nano silicon dioxide to obtain a powder mixed sample; mixing and stirring the powder mixed sample with water to obtain a wet material slurry; performing standard curing on the wet material slurry after pouring to obtain a test block; and performing carbonization curing on the test block to obtain a carbon-fixed high-water-resistant gypsum product.
10. The method for preparing the carbon-fixing highly water-resistant gypsum product according to claim 9, characterized in that: The carbonization curing time is 24 to 72 hours, the carbon dioxide concentration is 20% to 50%, and the temperature is 20±2°C.
Citation Information
Patent Citations
Preparation method of phosphogypsum-based high-fluidity water-resistant mortar
CN112645674A
Waterproof anti-mildew beta-type building gypsum plastering mortar and preparation method thereof
CN116082009A
Carbonization-cured high-strength coal gangue-based low-carbon baking-free grass planting brick and preparation method thereof
CN116119990A
Red mud-based foamed concrete and preparation method thereof
CN117645461A